Designing a Design Thinking Model in Interior Design Teaching and Learning - Suastiwi Triatmodjo (Journal of Urban Society's Arts, 2020)
In the last three decades, research on design processes and methods has been the driving force behind the design science development; however, research on design process knowledge has not developed much in Indonesia. This research aims to answer the problems faced by interior design students when they have to complete a design task by applying specific design processes and methods. The choice of technique and method is influenced by the situation & conditions in which the design is carried out. The research was carried out using the “double diamonds” process and method with a problem-solving approach. The research analysis was carried out by examining students’ design documents in the interior design course, conducting interviews with students and lecturers, and literature studies. Furthermore, an alternative process model and design method are more prepared to follow the needs and answer the Interior Design Study Program’s problems when completing a design task. Research has succeeded in finding process models and design methods called a DT-DI model compatible with interior design students.